Comparing the Heart–Thigh and Thigh–Ankle Arteries with the Heart–Ankle Arterial Segment for Arterial Stiffness Measurements - Watahiki, Manami (Vasc Health Risk Manag, 2020)
PURPOSE: The cardio-ankle vascular index, applying the stiffness parameter β theory, was calculated using the pulse-wave velocity and blood pressure from the aortic orifice to the ankle. Accordingly, the impact of the stiffness of the aorta [heart–thigh β (htBETA)] and medium-sized muscular artery [thigh–ankle β (taBETA)] on the stiffness of the heart–ankle β (haBETA) was investigated; further, whether the htBETA (haBETA − taBETA) improved the power of diagnosis of coronary artery disease (CAD) was examined. MATERIALS AND METHODS: Segmental βs were calculated using VaSela with an additional thigh cuff and compared using the receiver operating characteristic (ROC) curve analysis to evaluate CAD. RESULTS: Overall, 90 healthy subjects and 41 patients with CAD were included. In both groups, haBETA and htBETA, but not taBETA, correlated with age, and taBETA was three times higher than htBETA (p < 0.01). Multiple regression analysis revealed that haBETA can be estimated using htBETA and taBETA in healthy subjects and patients with CAD (r = 0.86, r = 0.67, respectively, p < 0.01), and two-thirds of the haBETA components can be estimated by htBETA using the component analysis. The area under the ROC curve (AUC) for CAD in taBETA (0.493, p = n.s.) was smaller than that in haBETA (0.731, p < 0.01) or htBETA (0.757, p < 0.01); no difference was observed in AUC between haBETA and htBETA. CONCLUSION: The stiffness of medium-sized muscular arteries of the age-independent thigh–ankle segment (taBETA) was constant, which was three times greater than that of the elastic artery of the heart–thigh artery (htBETA). Two-thirds of the haBETA components could be estimated using htBETA. The ROC curve analysis revealed that the AUC of haBETA could be replaced by that of htBETA, prolonging the measurement segment without affecting the diagnostic power for CAD.